Cultures of Victory and the Political Consequences of Foundational Legitimacy in Croatia and Kosovo. (October 2019) - Boduszyński, Mieczysław P.; Pavlaković, Vjeran
What are the consequences of a culture of victory in countries undergoing new state formation and democratic transition? In this article, we examine 'foundational legitimacy, ' or a hegemonic narrative about the way in which a new state was created, and the role particular groups played in its creation. We argue that the way in which victory is institutionalized can pose a grave threat to the democratic project. If reconciliation and democratization depend of integrating losers into the new order and recognizing plural narratives of state formation, then exclusivist narratives based on foundational legitimacy pose a direct challenge to both. We focus on two Yugoslav successor states, Kosovo and Croatia. For both cases, we trace how appeals to 'foundational legitimacy' by groups that claim a leading role in the struggle for independence fostered a politics of exclusion, which ran counter to both the spirit of democracy. In Croatia, foundational legitimacy was partly challenged after 2000 by reformist political forces, though more recently it has re-appeared in political life. In Kosovo, foundational legitimacy was never successfully challenged and continues to shape political dynamics to the present day.